The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1177/0165551519834714
|View full text |Cite
|
Sign up to set email alerts
|

A study of the determinants of postgraduate students’ satisfaction of using online research databases

Abstract: In today’s technology-enriched environment, online research databases have become an indispensable tool in learning and research activities. Libraries worldwide have incorporated them as an integral part of their current service delivery. This study intends to determine whether the technology satisfaction model (TSM) validly measures postgraduate students’ satisfaction of using online research databases in an academic library. It further explores the relationships among antecedents within the model. To measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 58 publications
(94 reference statements)
4
18
0
Order By: Relevance
“…Almost all LC-students find the e-course in mathematical methods in psychological and educational researches informative and practically useful. Considering the positive attitude expressed by the majority of students towards e-courses and online learning, including at partner universities, this result is in good agreement with the findings of ( Islam and Sheikh, 2020 ) and ( Wu and Chen, 2017 ).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Almost all LC-students find the e-course in mathematical methods in psychological and educational researches informative and practically useful. Considering the positive attitude expressed by the majority of students towards e-courses and online learning, including at partner universities, this result is in good agreement with the findings of ( Islam and Sheikh, 2020 ) and ( Wu and Chen, 2017 ).…”
Section: Discussionsupporting
confidence: 88%
“…The technology satisfaction model reported in ( Islam and Sheikh, 2020 ) shows the association of perceived usefulness, computer self-efficacy and perceived ease of use with postgraduate students' satisfaction of using online research databases. The results presented in ( Wu and Chen, 2017 ) show that students' perceived usefulness is a significant mediator of the effects of perceived ease of use, task technology fit, reputation, social recognition and social influence on continuance intention also using MOOCs.…”
Section: Introductionmentioning
confidence: 99%
“…It was later validated in a Chinese university to measure students’ satisfaction with using wireless internet in learning activities (Islam et al, 2018 ). In 2020, Islam and Sheikh ( 2020 ) validated the relationships within the TSM in a Pakistani university. However, the TSM has not been validated to assess online learning platform success.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In other words, it is probable that university students with high computer self-efficacy find it easy to use online learning platforms as well as realize their value and benefits. In view of this, Islam and Sheikh ( 2020 ) suggested that more attention should be paid to the assessment of computer self-efficacy and its impact on students’ perceived ease of use and usefulness. Therefore, we hypothesize the following: H1.…”
Section: Hypothesesmentioning
confidence: 99%
“…As a result of emerging educational technology, researchers have introduced the idea of "computer self-efficacy," which refers to lecturers' confidence in their ability to use new technologies (Islam, 2015). CSELE was found by many researchers to be associated with students' PEOU and PU of various ICT applications such as computer simulation (Liu & Huang, 2015), wireless internet (Islam, 2014;Islam et al, 2018), research databases (Islam & Sheikh, 2020), and electronic textbooks (Chiu, 2017). However, this association has not been frequently demonstrated in Chinese university lecturers' ICT use.…”
Section: Hypotheses Of the Tsm Modelmentioning
confidence: 99%